2008
DOI: 10.1590/s0102-76382008000300010
|View full text |Cite
|
Sign up to set email alerts
|

Benefícios da ventilação não-invasiva após extubação no pós-operatório de cirurgia cardíaca

Abstract: Benefícios da ventilação não-invasiva após extubação no pós-operatório de cirurgia cardíacaBenefits of non-invasive ventilation after extubation in the postoperative period of heart surgery Abstract Objective: to show the benefits of the use of non-invasive positive pressure ventilation (NPPV) in the process of weaning from mechanical ventilation in the immediate postoperative period of heart surgery.Methods: A prospective, randomized and controlled study was performed involving 100 consecutive patients submit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 18 publications
1
32
0
10
Order By: Relevance
“…The incidence of pulmonary complications of patients on the preoperative period can be noted on the 1 st postoperative day and on the 6th postoperative day. A greater number of radiographs changed on the 6 th postoperative day was found (78%) compared to the 1st postoperative day (40%), occurring on intubation, decrease of respiratory complications and thus resulting in reduced length of hospital stay associated with the reduction in hospital costs [5,8,10,20,21].…”
Section: Radiological Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of pulmonary complications of patients on the preoperative period can be noted on the 1 st postoperative day and on the 6th postoperative day. A greater number of radiographs changed on the 6 th postoperative day was found (78%) compared to the 1st postoperative day (40%), occurring on intubation, decrease of respiratory complications and thus resulting in reduced length of hospital stay associated with the reduction in hospital costs [5,8,10,20,21].…”
Section: Radiological Findingsmentioning
confidence: 99%
“…Lopes et al [21] showed in their study improvement in oxygenation of the patients in the immediate postoperative period of heart surgery, using noninvasive ventilation for 30 minutes after extubation when compared to the control group with nasal oxygen catheter.…”
Section: Radiological Findingsmentioning
confidence: 99%
“…Cardiac surgeries are major surgeries broadcasted worldwide, among them stands out mostly coronary artery bypass (CABG) and valve replacement [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The morbidity and mortality in the postoperative of cardiac surgeries is of great interest, prompting several protocols for postoperative management [1][2][3][4]. The ischemic asymptomatic episodes are very frequent and seem to imply a worse prognosis [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation